Demographic, Clinical, and Behavioral Factors Associated With Electronic Nicotine Delivery Systems Use in a Large Cohort in the United States - Shauna Goldberg Scott MPH; Heather S. Feigelson PhD, MPH; John David Powers MS; Morgan N. Clennin PhD, MPH; Jason A. Lyons MA; Mark T. Gray BS; Anil Vachani MD, MS; Andrea N. Burnett-Hartman PhD, MPH (SAGE Publishing, 2023)
Introduction Our primary purpose is to understand comorbidities and health outcomes associated with electronic nicotine delivery systems (ENDS) use. Methods Study participants were Kaiser Permanente (KP) members from eight US regions who joined the Kaiser Permanente Research Bank (KPRB) from September 2015 through December 2019 and completed a questionnaire assessing demographic and behavioral factors, including ENDS and traditional cigarette use. Medical history and health outcomes were obtained from electronic health records. We used multinomial logistic regression to estimate odd ratios (ORs) and 95% confidence intervals (CIs) of current and former ENDS use according to member characteristics, behavioral factors, and clinical history. We used Cox regression to estimate hazard ratios (HRs) and 95% CIs comparing risk of health outcomes according to ENDS use. Results Of 119 593 participants, 1594 (1%) reported current ENDS use and 5603 (5%) reported past ENDS use. ENDS users were more likely to be younger, male, gay or lesbian, and American Indian / Alaskan Native or Asian. After adjustment for confounding, current ENDS use was associated with current traditional cigarette use (OR = 39.55; CI:33.44-46.77), current marijuana use (OR = 6.72; CI:5.61-8.05), history of lung cancer (OR = 2.64; CI:1.42-4.92), non-stroke cerebral vascular disease (OR = 1.55; CI:1.21-1.99), and chronic obstructive pulmonary disease (OR = 2.16; CI:1.77-2.63). Current ENDS use was also associated with increased risk of emergency room (ER) visits (HR = 1.17; CI: 1.05-1.30) and death (HR = 1.84; CI:1.02-3.32). Conclusions Concurrent traditional cigarette use, marijuana use, and comorbidities were prevalent among those who used ENDS, and current ENDS use was associated with an increased risk of ER visits and death. Additional research focused on health risks associated with concurrent ENDS and traditional cigarette use in those with underlying comorbidities is needed.